Factors Impeding Islamic Religious Instructors' Communication in the Development of Mental Health, Spirituality, and Islamic Education for the Elderly - Rahmadianawati Rahmadianawati; Syukur Kholil; Ahmad Tamrin Sikumbang (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The purpose of this research is to determine the hurdles to Islamic Religion Counselors' communication patterns in supporting the mental, spiritual wellness and Islamic education of nursing home elderly residents. Phenomenology was used in this study. At the Nursing Home, Islamic Religious Counselors coach the elderly on mental and spiritual wellness. Their communication styles were investigated in this study. The author accumulated a library of material and photographs. In this study, informants are recruited using a purposeful way. As a result, these informants can be picked since they have a lot of knowledge and can supply researchers with enough information to conclude their investigation.The descriptive qualitative approach was employed in this study to collect data in the form of oral speech, writing, attitudes and behavior, and facts observed from the research subjects. The authors use the following data collecting instruments to make data collection easier: Interviewing Procedures, Observation Guide, and Audio Visual Equipment. Researchers used Miles and Huberman's interactive data analysis paradigm in this work, with data reduction (data reduction), data presentation (data display), and conclusion drawing/verification (conclusion drawing/verification) as implementation procedures.To improve the mental, spiritual health and Islamic education of the elderly, Islamic religious counselors at the nursing home must overcome physical, physiological, psychological, and semantic barriers. To the nursing home caretakers and Indonesian Islamic-style nursing facilities, use this research to improve the mental and spiritual health of the elderly. Local Social Service organizations, the Regional Government, and the Office of the Ministry of Religion of North Aceh Regency are anticipated to provide facilities and infrastructure to improve the welfare of the elderly at the nursing home